Effect of Different Capping Agent on the Preparation and Properties of CdS Nanoparticles by using Starch and Glucose - Salunke Pooja; Jain Preeti (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
In recent years, green synthesis of CdS nanoparticle has attracted a wide attention due to unique properties such as optical and electronic etc. In nature, CdS nanoparticle comes in II-VI group semiconductor and has a band gap of 2.4 eV. It is used in different applications such as Photonics, optoelectronics, biomedical fields, etc. In our work CdS nanoparticles were synthesized using the chemical precipitation method by green chemical route. The CdS nanoparticle were characterized by UV-Visible spectroscopy and X-ray diffraction (XRD) technique used for particle size determination. The particle size is determined by both theoretical and practicle methods. The conductivity measurement is done by TDS/digital conductivity meter. Conductivity of CdS nanoparticles is 0.14 m seimen and 0.04 m seimen by using glucose and starch as a capping agent. It is observed that by the doping the conductivity of nanoparticle increases.